Pengaruh Penerimaan Pajak Hotel dan Pajak Restoran Terhadap Pendapatan Asli Daerah (PAD) pada Badan Pengelolaan Pajak dan Retribusi Daerah Kota Medan - Arnida Wahyuni; Rinie Utara (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2018)
To carry out and carry out regional autonomy broadly and responsibly, regional authority and capability is needed to explore its own financial resources in order to carry out their functions effectively and efficiently in the field of government and public services to the community. With the stipulation of Hotel Tax and Retirement Tax Rates in accordance with Law Number 28 of 2009 Article 35 and Article 40 of 10%, then every hotel and restaurant will provide 10% of the income for hotel services and restaurant services to consumers who enjoy it. Hotel Taxes and Restaurant Taxes are part of the potential PAD sources in the city of Medan and provide a substantial contribution when viewed from the local tax component, because Medan City is the gateway to receiving the flow of local tourists and foreign tourists visiting the area North Sumatra tourist destination.The phenomenon th at occurred only at the level of 2014 Hotel Tax receipts and 2015 Restaurant Taxes which had reached the planned target. Where Hotel Tax receipts in 2014 amounted to Rp. 81,642,581,350.74 has exceeded the target of Rp. 81,500,000,000 or reach 100.17% and Restaurant Tax receipts in 2015 amounted to Rp. 124,409,617,130.10 has exceeded the target of Rp. 123,215,837,083 or reach 100.97%. The effect of the phenomenon indicates that the sources of Regional Original Income (PAD) such as Hotel Taxes and Restaurant Taxes continue to decline in previous years which resulted in the receipt of Regional Original Income (PAD) in 2011 to 2015 which did not always reach the target has been established